Primary issues on preparing will in Malaysia: focus on syariah and administrative issues / Siti Sarah Mohamad Sanusi - Mohamad Sanusi, Siti Sarah (2018)
The accumulated and unclaimed property, lack of understanding and confusing with other Islamic inheritance distribution and lack exposure among Muslim of institution services will are trying to deliver that it has becoming a growing concern. These difficulties cannot be resolved if each party do not takes into their respective roles in implementing it. This research aim is to identify the primary issues in preparing wills among Malaysian. Then, to scrutinize the syariah and administrative aspects on selected issues of wills and to suggest syariah and administrative solutions in the management process of wills in Malaysia. This research has been conduct by using qualitative method which obtained from observation data that has been made on the execution of wills at the Religious Council Islam of Selangor (MAIS) institution and documentation data from literature reading on journal, articles, books, thesis and online news. The data was analyzed that the community knowledge in syariah aspects of will and the way of administration of will in Malaysia. Also, this research also suggested several things so that the issues can be reduced. Researcher hopes that it will create awareness and open the eyes of many parties in understanding the importance of the will of knowledge. At the same time, researcher hope it can avoid problems and issues can be avoided for peace in a family, religion, and economy of Malaysia.